Pengaruh Perkembangan Teknologi dan Edukasi Pasar Modal Terhadap Minat Mahasiswa Berinvestasi di Pasar Modal - Cita Rizki; Yessy Shafira Danti Widyasari; Dwi Epty Hidayaty (Jurnal Ilmiah Wahana Pendidikan, 2023)
Today's technological developments have a major influence on the economic progress of a country and encourage the business sector to become more efficient and effective in carrying out business operations to achieve maximum results. The capital market and financial sector has indeed become one of the economic benchmarks in a country where thousands of companies are registered that trade their shares on the secondary market or stock exchange. The capital market is an alternative for students or investors to invest both in the short and long term. Stocks are one of the most popular and traded capital market financial products. Investment knowledge is an understanding that one must have about various aspects of investment, starting from basic knowledge of investment appraisal, the level of risk and the rate of return on investment.